2017
DOI: 10.1016/j.sjbs.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of different approaches to managing Meloidogyne incognita on green bean

Abstract: A greenhouse study was conducted to compare the relative efficacy of different approaches to managing on green bean. These approaches included chemical (fumigant, non-fumigant, seed dressing, and seed dip), biological (the egg-parasitic fungus, and the mycorrhizal fungus sp.), physical (soil solarization), and cultural (chicken litter and urea) methods. Accordingly, nine different control materials and application methods plus nematode-infected and non-infected controls were compared. Two important parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
0
8
0
2
Order By: Relevance
“…Nematode control effectiveness using Paecilomyces depends on the crop itself, as it affects fungal activity in many cases [ 163 ]. Thus, the use of an antagonist in combination with organic substances increases parasitism by Paecilomyces in both eggs and larvae of nematodes [ 164 ].…”
Section: Biological Control Of Diseases Caused By Nematodesmentioning
confidence: 99%
“…Nematode control effectiveness using Paecilomyces depends on the crop itself, as it affects fungal activity in many cases [ 163 ]. Thus, the use of an antagonist in combination with organic substances increases parasitism by Paecilomyces in both eggs and larvae of nematodes [ 164 ].…”
Section: Biological Control Of Diseases Caused By Nematodesmentioning
confidence: 99%
“…Meloidogyne spp. are also difficult to control with a single control method [11]. Several management strategies, including crop rotations, developing and planting resistant varieties, use of chemical nematicides, and biological and physical control measures, can be applied to control RKNs [12][13][14].…”
mentioning
confidence: 99%
“…P. lilacinum, T. harzianum, and V. clamydosporium, as fungal parasites of nematode eggs and adults (Rao 2007) as well as P. penetrans as a bacterial parasite (Chen et al 1996) were previously reported among the most potent measures used in this subject. In addition, urea and nitrogenous fertilizers are considered to be good nematicides when applied at levels as low as 300-400 mg/kg soil (Rodriguez-Kabana 1986;Alam 1992;Al-Hazmi and Dawabah 2014;Al-Hazmi et al 2017). Likewise, many previous studies have shown that organic and inorganic nitrogen amendments had a nematicidal effect against plant-parasitic nematodes (Rodriguez-Kabana 1986;Akhtar and Malik 2000;Oka 2010).…”
Section: Resultsmentioning
confidence: 99%